(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study evaluates the impact of two novel humic acid-based fertilizers, Ekogumin (a soil-applied organic amendment) and Novogumin (a foliar suspension), on the yield and phenological parameters of cotton (Gossypium hirsutum L. cv. S-6775) under varying planting densities. Conducted in Uzbekistan from June to September 2025, the experiment involved 12 variants: mineral fertilizer controls (variants 1–3), Ekogumin alone (variants 4–6), Ekogumin combined with Novogumin (variants 7–9), and Novogumin alone (variants 10–12), at densities of 150–160, 180–190, and 210–220 thousand plants/ha. Phenological observations (plant height, productive branches, flowers, bolls) were recorded monthly, culminating in yield assessments. Results indicate that Ekogumin alone increased yield by 8.5–9.5% over controls, the combination by 17.5–18.7%, and Novogumin alone by 6.0–7.0%, with synergistic effects evident in the combination. Higher densities amplified these benefits, though phenological gains were modest in the first month. These findings suggest humic acids enhance nutrient uptake and stress tolerance, supporting sustainable cotton production.